Co-Delivery of Epirubicin and siRNA Using Functionalized Mesoporous Silica Nanoparticles Enhances In vitro and In vivo Drug Efficacy - Yahya Hanafi-Bojd, Mohammad; Reza Jaafari, Mahmoud; Ramezanian, Navid; Abnous, Khalil; Malaekeh-Nikouei, Bizhan (Current Drug Delivery, 2016)
Development of drug resistance to anticancer drugs is an important challenge for cancer treatment. Recent studies focus on co-delivery of anticancer drugs and siRNA to overcome this challenge. Mesoporous silica nanoparticles (MSNs) are one of the promising nanoparticles that enable the delivery of drugs and siRNA simultaneously. MSNs coated with copolymer capable of co-delivery of drug and siRNA were prepared and characterized. In the present study, MSNs functionalized with polyethylenimine-polyethylene glycol (PEI-PEG) copolymer were prepared. MSNs were characterized using dynamic light scattering (DLS), Transmission Electron Microscopy (TEM) and elemental analysis. Nanoparticles were loaded with epirubicin hydrochloride (EPI) and anti B-cell lymphoma 2 (BCL-2) siRNA. The in vitro cytotoxicity and in vivo efficacy of different formulations were evaluated. Mean size of MSNs ranged from 98 to 247 nm. EPI release from MSNs was pH-dependent. MSNs loaded with EPI and siRNA showed better in vitro cytotoxicity with 1 μg/mL EPI and 50-400 ng/mL siRNA, besides MSNs loaded with 9 mg/kg EPI and 1.2 mg/kg siRNA resulted in improved in vivo effects compared to EPI or MSNs containing EPI or siRNA alone. The results of in vitro and in vivo studies indicated the synergistic effect of EPI and anti BCL-2 siRNA. This formulation could be a promising nanoparticle for codelivery of drug and siRNA in cancer cells.
Keywords: Cancer treatment